Organized Voters: Elections and Public Funding of Nonprofits - Urvoy, Camille (American Economic Review, 2025)
What makes politicians respond to civil society organizations' demands? I use new data on government transfers to French associations and exploit close elections to show that politicians grant more funds to ideologically close organizations when the local incumbent is a political ally and was elected by a small margin. The results are consistent with politicians and organizations exchanging financial support for electoral support. Organizations secure funding because of the votes they can deliver, not because of their campaign contributions; however, the fact that transfers appear to be conditioned on support may undermine their ability to help hold politicians accountable. (JEL D23, D72, H81, L31)